1994
DOI: 10.1002/jlb.55.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mycobacterial proteins during phagocytosis and heat shock: a time interval analysis

Abstract: Mycobacterium tuberculosis survives macrophage bactericidal activities by mechanisms that may include induction of stress proteins. We sought to determine whether the synthesis of any mycobacterial proteins is increased during phagocytosis and whether any of these proteins are also up-regulated during heat shock. Protein synthesis by M. tuberculosis H37Ra during phagocytosis by the mouse macrophage cell line IC-21, and during heat shock at 45 and 48 degrees C, was monitored at various time intervals using 35S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…The results presented in this paper with regard to the upregulation of GroEL-1\GroEL-2, appear to confirm those obtained in two previous studies which have examined the response of M. tuberculosis to intracellular residence within murine (Alavi & Affronti, 1994) and human (Lee & Horwitz, 1995) macrophages. In both of these studies, it was revealed that Hsp65 was up-regulated within the mouse IC-21 cell line (Alavi & Affronti, 1994), while the expression of both Hsp65 and Hsp70 was observed to have increased upon intracellular residence within the human THP-1 cell line (Lee & Horwitz, 1995).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results presented in this paper with regard to the upregulation of GroEL-1\GroEL-2, appear to confirm those obtained in two previous studies which have examined the response of M. tuberculosis to intracellular residence within murine (Alavi & Affronti, 1994) and human (Lee & Horwitz, 1995) macrophages. In both of these studies, it was revealed that Hsp65 was up-regulated within the mouse IC-21 cell line (Alavi & Affronti, 1994), while the expression of both Hsp65 and Hsp70 was observed to have increased upon intracellular residence within the human THP-1 cell line (Lee & Horwitz, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…It also has homologues of the Yersinia invasin and Listeria internalin genes, mce (Arruda et al, 1993), as well as genes which are differentially expressed in the virulent phenotype (Kinger & Tyagi, 1993). Furthermore, a gene (mig) encoding a secreted protein has been identified as being specifically induced by Mycobacterium avium inside macrophages (Plum & Clark-Curtiss, 1994 ;Plum et al, 1997), and both virulent and avirulent strains of M. tuberculosis and M. avium have been shown to express a series of differentially expressed proteins in response to infection of either murine or human macrophages (Alavi & Affronti, 1994 ;Lee & Horwitz, 1995 ;SturgillKoszycki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…To detect Rv1988 in the host cell without lysing the mycobacterial cell wall, cell lysate was prepared in an NTEN buffer containing 0.5% NP-40 (infected mycobacterial cells are known to remain intact in this buffer 23 ) and probed for the presence of Rv1988 using 6X His antibody. Rv1988 was indeed detected in this infected THP1 cell lysate ( Supplementary Fig.…”
Section: Lower Panel)mentioning
confidence: 99%
“…3c). Forty-eight hours after infection, subcellular fractionation of the infected THP1 macrophages 24 was performed taking care that intracellular mycobacterial cells did not lyse 23 . Rv1988-6XHis was detected only in the chromatin fraction (Fig.…”
Section: Lower Panel)mentioning
confidence: 99%
“…During replication within the cytoplasm, stress proteins of L. monocytogenes are not induced, which indicates that the cytoplasmic 'microenvironment' does not contain conditions adverse to microorganisms (Hanawa et al, 1995). In contrast, other facultative intracellular pathogens, such as Salmonella typhimurium, Mycobacterium tuberculosis, Yersinia entercolitica, Brucella abortus, and L. pneumophila, reside within a vacuole and manifest an induction in the synthesis of numerous proteins in response to the vacuolar 'microenvironment' (Lee and Horwitz, 1995;Abu Kwaik et al, 1993;Buchmeier and Heffron, 1990;Abshire and Neidhardt, 1993;Garcia-del Portillo and Finlay, 1995;Fernandez et al, 1996;Alavi and Affronti, 1994;Yamamoto et al, 1994;Rafie-Koplin et al, 1996;Chen et al, 1996). At least 30% of the macrophage-induced (MI) proteins expressed by these pathogens are also induced by one or more in vitro stress stimuli, but none of these stimuli can mimic the intracellular microenvironment (Lee and Horwitz, 1995;Abu Kwaik et al, 1993;Buchmeier and Heffron, 1990;Abshire and Neidhardt, 1993;Garcia-del Portillo and Finlay, 1995;Rankin and Isberg, 1995;Rafie-Koplin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%